Automatic gnetum nut’s puncher machine using pneumatics pressure / Alfiandis Lafebri … [et al.] - Lafebri, Alfiandis; Raja Adrafi, Muhammad; Nehe, Alva Nikodemus; Nurita, Nurita; Hendriko, Hendriko (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Indonesia produces a large number of gnetum nuts, and mostly they are processed to be chips. Gnetum chip is one of Indonesia's favorite food. Gnetum chip is not only marketed in Indonesia, but they have been exported to various countries including the Netherlands, United State of America, and the Middle East. Mostly gnetum chips are produced traditionally by the home industry and MSMEs. The existing machines to produce gnetum chips are not equipped with an automatic system; hence they still require significant operator involvement. This invention used a pneumatics pressure as a power driver. Pneumatic cylinders are used to push the gnetum nut onto the flattening base, and to move the puncher rod during the flattening process. The pusher rod put the gnetum rod to the base, and simultaneously remove the flattened nut to the basket. The machine has been tested, which was carried out to determine the parameters used for programming the machine, such as punching time and pneumatic pressure, and for checking the capacity of the machine. The test results show that the most effective punching time is 5 seconds at a pressure between 5-7 bar. In 5 seconds, the machine can change the gnetum nut into a chip shape with a thickness in between 1,20-1,45 mm. The capacity of the machine in processing gnetum nut has also been tested. The results showed that this machine can process 528 gnetum nuts into chips shape gnetum per hour. This machine is suitable for small to medium industries.